The Advantages and Disadvantages of E-Commerce Tax and Income Tax for the Indonesian Economy and the Welfare of MSMEs in Indonesia - Gusneli, Gusneli; Asry, Shofia; Sugiarti, Sri; Mawaddah, Mawaddah; Handa, Adrian (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2025)
The rapid growth of the digital economy in Indonesia has shifted the transaction paradigm from conventional to e-commerce platforms , which brings new challenges to the national tax system. This article aims to analyze the advantages and disadvantages of implementing e-commerce taxes and Income Tax (PPh) on Indonesia's economic stability and their impact on the welfare of Micro, Small, and Medium Enterprises (MSMEs). Through a systematic literature review and descriptive analysis, this study found that imposing taxes on the digital sector can create a fair competition ( level playing field ) between online and offline businesses and significantly increase state revenue. However, on the other hand, administrative burdens and the potential for reduced competitiveness are major challenges for MSMEs still in the economic recovery phase. The study concludes that although tax policies are necessary for fiscal sustainability, the government needs to implement progressive tariff policies and simplify the tax bureaucracy to maintain a balance between state revenue targets and the sustainability of MSMEs as the backbone of the national economy.